Corrosion of Platinum Nanocoatings Thin Films Deposited by Sputtering Deposition Method for Medical Applications - Haitham M. Wadullah, Asst. Prof. Dr.; Sami Abualnoun Ajeel, Prof.Dr.; Muna Khethier Abbass, Prof.Dr .; Mohammed Younus Hussein, Eng .; ., . (International Journal of Engineering and Technology, 2018)
Platinum (Pt.) thin films have been deposited by Magnetron Sputtering Deposition method with 25 nm and 50 nm thickness by used power RF for deposited 5 nm Titanium (Ti) firstly then used DC for deposited Platinum (Pt) on Ni-Cr alloy substrate. SEM/EDX and Ellipsometry Spectroscopy have been used to investigate the morphology, element analysis, nanothickness and roughness of the thin films respectively. Electrochemical corrosion tests have been used to analyze the localized corrosion resistance by used cyclic polarization, Tafel extrapolation and open circuit potential (o.c.p) methods on artificial saliva solution at 37  ±1 oC. The results show the ability to deposit 5 nm of Ti before deposited of Pt. film to improve the adhesive of the films, nanostructure morphology of the Pt. film without defect or microcracks, nanocoatings thickness of Pt. film, and high localized corrosion resistance in artificial saliva corrosive media.